Pengembangan Model Pembelajaran Untuk Meningkatkan Kemampuan Mengajar Calon Guru Fisika - Lia Yuliati (Universitas Negeri Malang, 2016)
This research and development study aims at investigating the effectiveness of an instructional model in improving teaching competencies of physics teacher candidates. The data were collected through observation, tests, portfolios, and field notes, and then analyzed using gain-score and Z-test. The study shows that the model being developed improves students' competencies in designing, implementing, and evaluating instructions, as the model integrates knowledge of physics concepts to methods of teaching them; it is more practical; and it is teacher-candidate centered.